2013
DOI: 10.1016/j.cell.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Siglec-G by RNA Viruses Inhibits the Innate Immune Response by Promoting RIG-I Degradation

Abstract: RIG-I is a critical RNA virus sensor that serves to initiate antiviral innate immunity. However, posttranslational regulation of RIG-I signaling remains to be fully understood. We report here that RNA viruses, but not DNA viruses or bacteria, specifically upregulate lectin family member Siglecg expression in macrophages by RIG-I- or NF-κB-dependent mechanisms. Siglec-G-induced recruitment of SHP2 and the E3 ubiquitin ligase c-Cbl to RIG-I leads to RIG-I degradation via K48-linked ubiquitination at Lys813 by c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
254
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 241 publications
(257 citation statements)
references
References 49 publications
2
254
0
1
Order By: Relevance
“…This finding is of importance, as functions for Siglec-G on these DCs were indicated as important for preventing inflammatory responses in a liver damage model as well as for antibacterial responses (9,10). A recent study also showed that Siglec-G was induced in macrophages by RNA viruses and that this Siglec-G upregulation was important for innate immune responses against RNA viruses (19). Whether Siglec-G can be induced on the surface of macrophages was not addressed in this study but can easily be done with the new mAb in the future.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is of importance, as functions for Siglec-G on these DCs were indicated as important for preventing inflammatory responses in a liver damage model as well as for antibacterial responses (9,10). A recent study also showed that Siglec-G was induced in macrophages by RNA viruses and that this Siglec-G upregulation was important for innate immune responses against RNA viruses (19). Whether Siglec-G can be induced on the surface of macrophages was not addressed in this study but can easily be done with the new mAb in the future.…”
Section: Discussionmentioning
confidence: 88%
“…The control small RNA sequence was 5′-TTCTCCG-AACGTGTCACGT-3′. siRNA duplexes were transfected into mouse peritoneal macrophages using INTERFERin reagent (Polyplus) (37).…”
Section: Methodsmentioning
confidence: 99%
“…26 In brief, lungs were inflated with 4% paraformaldehyde, embedded in paraffin, sectioned and stained with H&E.…”
Section: Histological Analysismentioning
confidence: 99%